Influential Mechanisms of Roughness on the Cyclic Shearing Behavior of the Interfaces Between Crushed Mudstone and Steel-Cased Rock-Socketed Piles - Yue Liang; Jianlu Zhang; Bin Xu; Zeyu Liu; Lei Dai; Kui Wang (Buildings)
In the waterway construction projects of the upper reaches of the Yangtze River, crushed mudstone particles are widely used to backfill the foundations of rock-socketed concrete-filled steel tube (RSCFST) piles, a structure widely adopted in port constructions. In these projects, the steel–mudstone interfaces experience complex loading conditions, and the surface profile tends to vary within certain ranges during construction and operation. The changes in boundary conditions and material profile significantly impact the bearing performance of these piles when subjected to cyclic loads, such as ship impacts, water level fluctuations, and wave-induced loads. Therefore, it is necessary to investigate the shear characteristics of the RSCFST pile–soil interface under cyclic vertical loading, particularly in relation to varying deformation levels in the steel casing’s outer profile. In this study, a series of cyclic direct shear tests are carried out to investigate the influential mechanisms of roughness on the cyclic behavior of RSCFST pile–soil interfaces. The impacts of roughness on shear stress, shear stiffness, damping ratio, normal stress, and particle breakage ratio are discussed separately and can be summarized as follows: (1) During the initial phase of cyclic shearing, increased roughness correlates with higher interfacial shear strength and anisotropy, but also exacerbates interfacial particle breakage. Consequently, the sample undergoes more significant shear contraction, leading to reduced interfacial shear strength and anisotropy in the later stages. (2) The damping ratio of the rough interface exhibits an initial increase followed by a decrease, while the smooth interface demonstrates the exact opposite trend. The variation in damping ratio characteristics corresponds to the transition from soil–structure to soil–soil interfacial shearing. (3) Shear contraction is more pronounced in rough interface samples compared to the smooth interface, indicating that particle breakage has a greater impact on soil shear contraction compared to densification.